2011
DOI: 10.1002/ijc.25469
|View full text |Cite
|
Sign up to set email alerts
|

Liver specific overexpression of platelet‐derived growth factor‐B accelerates liver cancer development in chemically induced liver carcinogenesis

Abstract: A genetic basis of hepatocellular carcinoma (HCC) has been well-established and major signaling pathways, such as p53, Wnt-signaling, transforming growth factor-b (TGF-b) and Ras pathways, have been identified to be essential to HCC development. Lately, the family of platelet-derived growth factors (PDGFs) has shifted to the center of interest. We have reported on spontaneously developing liver fibrosis in PDGF-B transgenic mice. Since HCC rarely occurs in healthy liver, but dramatically increases at the cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 40 publications
0
41
2
Order By: Relevance
“…Dissecting the effect of Asp/Clo on all these factors in our system is beyond the scope of this report. It is worth mentioning, however, that PDGF and serotonin have been reported to support HCC development in mice exposed to diethylnitrosamine (31) or to CCl 4 (32), respectively, two situations in which carcinogenesis is independent of adaptive immune responses and, as shown here for CCl 4 -treated mice, might not be influenced by antiplatelet therapy. Although indirectly, this may argue against the hypothesis that Asp/Clo-dependent amelioration of HCC in mice with immune-mediated chronic hepatitis reflects inhibition of PDGF-and serotonin-dependent pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Dissecting the effect of Asp/Clo on all these factors in our system is beyond the scope of this report. It is worth mentioning, however, that PDGF and serotonin have been reported to support HCC development in mice exposed to diethylnitrosamine (31) or to CCl 4 (32), respectively, two situations in which carcinogenesis is independent of adaptive immune responses and, as shown here for CCl 4 -treated mice, might not be influenced by antiplatelet therapy. Although indirectly, this may argue against the hypothesis that Asp/Clo-dependent amelioration of HCC in mice with immune-mediated chronic hepatitis reflects inhibition of PDGF-and serotonin-dependent pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Because PDGF also activates the PI-3 kinase and Ras-MAPK pathways [31] , PDGF-BB may induce de novo synthesis of ␤ -catenin via these pathways. Furthermore, Maass et al [32] reported that PDGF-B overexpression induces ␤ -catenin upregulation in the liver. These reports suggest that ␤ -catenin upregulation was induced by PDGF-B also in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that PDGF-B signaling accelerates the carcinogenesis in the fibrotic livers (Maass et al, 2011). Therefore, vaccination against PDGF-B for chronic liver diseases might have dual benefits of both suppressing fibrosis and preventing carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%